IDEOLOGY AND LEGAL DISCOURSE DURING ALBANIAN COMMUNISM - SKËNDERI RAKIPLLARI, Elsa (Comparative Legilinguistics, 2017)
This paper aims to explore the traces of ideology in court decisions from the Communism period in Albania. A court judgment on a certain case, except from playing a role in setting the punishment, it also reinforces the ideological stance of dictatorship. As recent studies of Discourse Analysis and Critical Discourse Analysis highlight, ideology is linguistically mediated. The CDA methodological tools are used to analyze the linguistic categories that are marked by ideological traces. The paper also examines conceptual metaphors and the metaphoric scenarios employed in the above legal discourse fragments, which help communism construct its own legal and political reality. All the findings of this research prove that ideology outreaches the political realities, and it may also affect the legal discourse, especially during the lead of a communist dictatorship.